2021
DOI: 10.3389/fpsyg.2021.766422
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship Between Corporate Social Responsibility, Trust, Corporate Reputation, and Brand Equity

Abstract: The purpose of this study is to investigate the relationship between corporate social responsibility (CSR), corporate reputation (CR), and brand equity (BE). Building on the resource-based theory of the firm, this study proposes a theoretical framework. In this framework, CSR is theorized to strengthen CR and brand equity, directly and indirectly, through consumer trust. We used a questionnaire survey approach. In the questionnaire, 17 items were used with a 5-point Likert-Scale (1 stands for “strongly disagre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 74 publications
1
9
0
1
Order By: Relevance
“…In accordance with this result, previous studies have demonstrated the importance of CSR in improving corporate sustainability performance and promoting organizational development (Crișan-Mitra et al, 2020;May et al, 2021;Vătămănescu et al, 2021). Besides, the study extends understanding of the antecedents and consequences of CSR (Pasricha et al, 2018;Memon et al, 2021;Shen et al, 2021;Zhao et al, 2021). Furthermore, it is very interesting that the mediating role of CSR connects upper echelons theory and SIP theory.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…In accordance with this result, previous studies have demonstrated the importance of CSR in improving corporate sustainability performance and promoting organizational development (Crișan-Mitra et al, 2020;May et al, 2021;Vătămănescu et al, 2021). Besides, the study extends understanding of the antecedents and consequences of CSR (Pasricha et al, 2018;Memon et al, 2021;Shen et al, 2021;Zhao et al, 2021). Furthermore, it is very interesting that the mediating role of CSR connects upper echelons theory and SIP theory.…”
Section: Discussionsupporting
confidence: 82%
“…Upper echelons theory states that CEO characteristics determine strategic choices and performance consequences of enterprises ( Hambrick and Mason, 1984 ). As a key strategic choice, CSR is the integration of social welfare, business models, and investment patterns ( Barnett, 2007 ; Zhao et al, 2021 ). The business objective of a company is to maximize shareholder wealth.…”
Section: Theories and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, numerous scholars have identified major factors that impact FI, such as stakeholder expectations, competitive forces and consumer desires, business ethics, and environmental awareness. In order for a company to survive, FI assessment and its aspects are considered essential ( Shibin et al, 2018 ; Zhao et al, 2021 ). A competitive advantage is not the only advantage FI offers today.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%